Mechanical thrombectomy of acute distal posterior cerebral artery occlusions. (June 2021) - Miszczuk, Milena; Bauknecht, Hans Christian; Kleine, Justus F.; Kabbasch, Christoph; Liebig, Thomas; Bohner, Georg; Siebert, Eberhard
Highlights: MTE for acute distal PCA occlusion appears both safe and angiographically effective. Common MTE techniques developed can also be applied to distal PCA MTE. Clinical effectiveness remains to be determined by further studies. Abstract: To describe our experience with mechanical thrombectomy (MTE) of acute distal posterior cerebral artery (PCA) occlusions, either isolated or in combination with more proximal vessel occlusions regarding recanalization rates, MTE techniques, and procedural safety. From the prospectively maintained stroke thrombectomy databases of two institutions, all consecutive patients subjected to MTE of acute distal PCA occlusion (P2 and 3 segments) between July 2013 and May 2020 were retrospectively identified. Imaging data and angiographic features, as well as patients' demographic and clinical data were evaluated. 35 consecutive patients were included in the study. In 17 patients MTE of isolated acute distal PCA occlusion was performed. 9 patients had combined basilar artery (BA) and distal PCA occlusion on stroke imaging and 3 had embolic distal PCA occlusion following MTE for BA occlusion. 6 patients harbored distal PCA occlusions in combination with carotid-T occlusion and a dominant posterior communicating artery. The median NIHSS at presentation was 14 (IQR 8 – 27). 25 patients (71.4%) had occlusions of the P2 and 10 patients (28.6%) of the P3 segment. Successful recanalization (TICI 2b/3) was achieved in 31 patients (88.6%). 10 patients (28.6%) were treated with a direct contact aspiration technique, while a stent retriever was used in 25 patients (71.4%). No complication attributable to distal PCA MTE occurred. Good outcome (mRS ≤ 2) was achieved in 14 patients (46.7%) and mortality was 22.9%. MTE for acute distal PCA occlusion in the setting of different occlusion patterns appears both safe and angiographically effective. Yet, clinical effectiveness remains to be determined.